Prevalence of snake bites in Kangar district Hospital, Perlis, West Malaysia: a retrospective study (January 1999-December 2000) - Jamaiah, I.; Rohela, M.; Roshalina, R.; Undan, R.C. (SEAMEO Regional Tropical Medicine and Public Health Network, 2004)
The records of 284 snake bite cases presenting to the Kangar District Hospital, Perlis, West Malaysia, from January 1999 till December 2000 were carefully reviewed. Data on prevalence and types of snake bites, were recorded. The majority of the cases were among Malays (60.2), followed by Chinese (16.9), Indians (13), and others which include Thai nationals, army personnel from Sabah and Sarawak, and foreign tourists (9.8). A higher incidence was found in males (60.2) and most cases were seen in the age group of 10-19 years (33). Snake bites were more common between 2 PM and 9 PM (47.6) and from 7 AM to 2 PM (33.4). The snakes were positively identified in 68 cases, of which 50 were common cobras (Naja naja) (73), 16 were Malayan pit vipers (Agkistrodon rhodostoma) (24) and two were sea-snakes (3).